Kajian Ekspor Impor dan Variabel Makro Ekonomi terhadap Pergerakan Harga Saham Pertanian - Irianto Irianto; Baiq Kisnawati; Istiarto Istiarto; Zulkarnaen Zulkarnaen (Valid: Jurnal Ilmiah, 2021)
This study aims to examine the effect of exports, imports and macroeconomic variables on the movement of the stock price index of the agricultural sector listed on the Indonesia Stock Exchange. The sampling technique used was a saturated sample. The research data were secondary data for the 2000-2019 observation period. Data were analyzed using Multiple Linear Regression with SPSS application. Hypothesis testing was carried out by t-test for partial testing and testing the coefficient of determination. The results showed that partially the export variable had a positive and insignificant effect, imports had a positive and insignificant effect, the rupiah exchange rate had an insignificant negative effect, inflation had a non-significant positive effect, and bank interest rates had an insignificant negative effect on the stock price index of the agricultural sector. The ability of the independent variable is only able to explain 50.60% of the stock price of the agricultural sector, the remaining 49.40% is influenced by other variables outside the model. This means that the variables studied in this study are not sufficient to explain the dependent variable, so that potential investors are strongly encouraged to consider other variables before making investment decisions